A question of character : scientific racism and the genres of American fiction, 1892-1912 - Boeckmann, Cathy, 1968- (Tuscaloosa : University of Alabama Press, 2000)
"In A Question of Character, Cathy Boeckmann establishes a strong link between racial questions and the development of literary traditions at the end of the 19th century in America. This period saw the rise of "scientific racism," which claimed that the races were distinguished not solely by exterior appearance but also by a set of inherited character traits. As Boeckmann explains, this emphasis on character meant that race was not only a thematic concern in the literature of the period but also a generic or formal one as well." "Boeckmann explores the intersections between race and literary history by tracing the language of character through both scientific and literary writing."--Jacket
Acknowledgments -- Introduction -- Scientific racism, character, and American fiction -- Thomas Dixon and the rhetorical mulatto -- Pudd'nhead Wilson's phrenological photograph -- Howells and Chesnutt: the racial uses of genre -- Character and black art in The autobiography of an ex-Coloured man -- Epilogue: race and representation -- Notes -- Works cited -- Index.
Includes bibliographical references (pages 227-233) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: American fiction -- 19th century -- History and criticism; Racism in literature; American fiction -- 20th century -- History and criticism; Literature and science -- United States -- History; Characters and characteristics in literature; Race discrimination in literature; Passing (Identity) in literature; African Americans in literature; Eugenics in literature; Literary form; Roman américain -- 19e siècle -- Histoire et critique; Racisme dans la littérature.; Roman américain -- 20e siècle -- Histoire et critique; Littérature et sciences -- États-Unis -- Histoire; Discrimination raciale dans la littérature.; Passing (Identité) dans la littérature.; Noirs américains dans la littérature.; Eugénisme dans la littérature.; Genres littéraires.; LITERARY CRITICISM -- American -- General; African Americans in literature; American fiction; Characters and characteristics in literature; Eugenics in literature; Literary form; Literature and science; Passing (Identity) in literature; Race discrimination in literature; Racism in literature; United States; American Literature; English; Languages & Literatures; 1800-1999; Criticism, interpretation, etc; History